P056 Using Polysomnography in Young People with Borderline Personality Disorder: A Pilot and Feasibility Study. (7th October 2021) - Jenkins, C; Thompson, K; Chanen, A; Nicholas, C
Abstract: Introduction: Few studies have assessed sleep in young people (aged 15–25 years) with BPD using polysomnography. The feasibility of using polysomnography in this population might be questioned due to polysomnography's invasiveness, anxiety and sensory sensitivities in BPD, and misconceptions that individuals with BPD are uncooperative and non-compliant. This study aimed to provide pilot sleep quality and architecture data and assess polysomnography feasibility. Method: Participants were 13 females aged 15–25, 7 (Mage = 19.97, SD = 3.15) with BPD and 6 age-matched healthy controls (Mage = 20.13, SD = 3.31). Participants completed two non-consecutive nights of polysomnography monitoring (second night's data were used in analyses). Participants were given the option of completing polysomnography monitoring at home or in a sleep laboratory. Results: Young people with BPD displayed less arousals across the night and specifically during NREM sleep compared with healthy young people. All other sleep parameters were comparable across groups. There was considerable heterogeneity among participant preferences for in-home vs. sleep laboratory-based monitoring, due to comfort, safety, convenience, interest in seeing a sleep laboratory, or their living situation (eg. presence of bed partner at home). Anxiety was identified as a potential barrier to polysomnography research in this population. Discussion: There were some indications of more consolidated sleep in BPD, which might reflect a greater sleep need in this population. The feasibility and tolerability of in-home and sleep laboratory-based polysomnography were demonstrated. Future protocols should incorporate ways to minimise anxiety, for example through providing a choice of monitoring location.